Repair of traumatic defect of lower lip using Estlander technique and commisuroplasty in Cameroon - Brian Zilefac Ngokwe; Karl Kwedi; Guiliane Djoumekoum; Alex Franklin Diffo; Max Lessle (Elsevier, 2021)
Human bite is a challenging public health concern. It may be seen in both victims and aggressors following assault.Lips are structures that play an essential role in aesthetics and in different functions such as nutrition and speech.Treatment of these defects can be complex and have significant impact on the patient's facial function and aesthetics.The goals of lip reconstruction include maintenance of oral competence, sufficient oral access, adequate tissue match in terms of colour and texture, proper symmetry as well as preservation of the apparent commissure and sensation.The use of flaps for the reconstruction of large defects with low risk of necrosis is possible given the abundant blood supply of the lips.We report a case of surgical reconstruction of the lower lip using the Estlander technique in a 53-year-old man following a traumatic human bite. We proceeded with a reconstruction using the Estlander technique followed by a commisuroplasty to respect facial symmetry.